THE FACEBOW IN THE CONTEXT OF PROSTHETIC THERAPY OF TOTALLY EDENTULOUS PATIENTS THROUGH CONVENTIONAL PROSTHESES - Kamel Earar; Alina-Ramona Dimofte; Norina Consuela Forna; Roxana Mihaela Dragan; Alina-Daniela Lepadatu; Ion Salagub; Marius Vacaru Carnaru; Vasile Hutanu; Oleg Solomon (Romanian Society of Oral Rehabilitation, 2024)
The prosthetic therapy of totally edentulous patients represents a constant challenge for the dentist, involving not only the restoration of masticatory and aesthetic function, but also the restoration of a biomechanical and anatomical harmony in a complex clinical setting. The occlusal schemes proposed for total dentures have significant differences compared to those found in most natural dentitions. The prostheses are characterized by distinct features and the occlusal configuration is designed with the aim of providing stability. In this perspective, the mounting of the facebow becomes a crucial element in the process of evaluating and planning prosthetic therapy in this category of patients. Total edentulous patients have significant anatomical and functional peculiarities, and the precise determination of intermaxillary relationships and jaw position in relation to the base of the skull becomes essential for obtaining successful therapeutic results. The mounting of the facebow is thus imposed as a fundamental technique, providing crucial information on the orientation of the jaw and contributing to the individualization of the treatment plan.